2009
DOI: 10.1103/physrevb.80.094408
|View full text |Cite
|
Sign up to set email alerts
|

Crystal lattice desolvation effects on the magnetic quantum tunneling of single-molecule magnets

Abstract: High-frequency electron paramagnetic resonance ͑HFEPR͒ and alternating current ͑ac͒ susceptibility measurements are reported for a new high-symmetry Mn 12 OH complexes. These comparisons reveal important insights into the factors that influence the values of the effective barrier to magnetization reversal, U ef f , deduced on the basis of ac susceptibility measurements. In particular, we find that variations in U ef f can be correlated with the degree of disorder in a crystal which can be controlled by desolv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 53 publications
1
57
2
Order By: Relevance
“…high and low symmetry, slow and fast relaxing, integer and odd-integer spin, etc.. This flexibility has, itself, yielded important insights into the magnetization dynamics associated with SMMs and, hence, to many more studies of Mn 12 compounds [8,9,39,40].…”
mentioning
confidence: 99%
“…high and low symmetry, slow and fast relaxing, integer and odd-integer spin, etc.. This flexibility has, itself, yielded important insights into the magnetization dynamics associated with SMMs and, hence, to many more studies of Mn 12 compounds [8,9,39,40].…”
mentioning
confidence: 99%
“…In all cases where the FR species are obtained in single-crystal form, X-ray studies show that one or more of the Jahn-Teller (JT) elongation axes associated with the Mn III atoms are abnormally oriented 18,19,21,24,25,33 in comparison to the usual SR form of Mn 12 . 26,27,[34][35][36][37] This is illustrated in Fig. 1 21,38 these complexes also exhibit fast magnetization relaxation.…”
Section: Introductionmentioning
confidence: 76%
“…The first point to note is that the ZFS is less than for highsymmetry SR Mn 12 , for which the known examples give values in the 300-307 GHz range. 34,35,62 Consequently, one may conclude that the reduction in ZFS is, at most, 10% for FR-Mn 12 tBuAc relative to SR Mn 12 , in spite of the fact that the barrier is ~40% lower.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…However we have shown that full removal of the acetic acid of crystallisation resolves the disorder in the O atoms of the acetate ligands, producing species that have true, unbroken S 4 symmetry. We expect 2 and 3 to exhibit similar QTM dynamics [32][33][34][35] to other fully axial analogues in the Mn 12 family: Mn 12 -tBuAc and Mn 12 -BrAc. Hence, we are refining the single-crystal to single-crystal method used to produce species 2 and 3, in order that we can selectively produce pure samples of either material for further study.…”
mentioning
confidence: 99%